La ausencia de norma expresa en la Ley Orgánica De Participación Ciudadana para la conformación de las instancias locales de participación vulnera los principios constitucionales de deliberación pública y autonomía de las organizaciones sociales - Celi Guato, Hernán Bolívar (2015)
This research raises the urgency of establishing an express provision for the formation of local instances of participation so that regulates the discretionary authority in their appeals. As such, it requires a study from the conceptual, doctrinal and legal, to justify the implementation of a reform that accounts for the generation of a real system of citizen participation, which in turn requires the same social network organizations internal democratization process to strengthen them. In this context, the framework provides definitions from the field of political science at being addressed as related to the state, the nation, civil society, development, political organization and social organization. Meanwhile in terms of constitutional law related meanings neoconstitutionalism, democracy, civic participation, autonomy and public deliberation is addressed. On the side of the doctrinal framework, the opinion of the different writers in the field of law, philosophy and sociology disciplines are interrelated for the study of human behavior in different historical periods is reviewed. In this chapter the development of democracy and its relationship with society is analyzed, and the existing power groups, starting with the family as the basic expression of social organization in the territory, through the Athenian city-state emerges as the most advanced political organization with the emergence of the state, appearing for the first time the concept of democracy as a form of management that, until our days when the term of democracy itself struggles to the extent that it excludes decisions most important to the majority of society, whose presence is reduced only to the electoral field. In this period growing demands of social organizations demanding transparency in the management of greater social control authorities and begins to struggle on the dimension of democracy, currents appear defend a model of representative democracy delegating political subjects solution social needs; and participatory democracy whose essence lies in the presence of citizens in decision-making and social control of the rulers and their management. Regarding the legal framework legislation containing provisions on public participation such as the Organic Code of Planning and Public Finance, the Organic Code of Territorial Organization, Autonomy and Decentralization, Organic Law of Citizen Participation and especially is reviewed Constitution of the Republic guarantees the mainstreaming of citizen participation, which reached maximum expression in generating institutions like Transparency and Social Control that comprise the Council of Citizen Participation and Social Control and enforcement agencies in this Standard Fundamental. In the field of comparative law it has been collected Bolivian, Nicaraguan and Venezuelan legislation because they contain standards for public participation in the field of management of local governments, to which our legal system are called Autonomous Decentralized Governments. It has not been included in the analysis of comparative law to Argentina, Colombia, Chile and Peru, containing legal bodies that regulate citizen participation in the framework of electoral processes regarding the citizens' legislative initiative and the removal of office, but no established regulatory processes of interaction with local authorities and civil society organizations in those territories. The legislation refers to the integration of local instances of citizen participation, guarantees individual and collective presence of citizens; however, it is accurate to highlight the importance of social organizations as managers of public policy, and because they are collected individual aspirations. Therefore emphasizes the importance of strengthening social organizations, respecting their autonomy in relation to state bodies. With these considerations, the research proposes an amendment to the Organic Law of Citizen Participation that allows to improve the levels of participation of social organizations on the basis of autonomy, that is, organizations can decide which areas involved and with whom. In other words, proactively it exercises the right of association, without discretionary authority in shaping convene the participation instances, but are the result of the desirability of the social partners and individuals. A reform at the same time identify with clarity what are the modalities of participation in the territory and differentiate internal organizational structures that stimulate their functioning; and to harmonize the various provisions that refer to instances of participation, especially as regards the legislative act to formalize its presence both at the level of planning and the budgeting. The urgency of reform is based on the requirement of most leaders of social organizations through a survey made by the investigator on the need for a change in the law made visible to account for a deepening of democracy from the perspective relations with the local authority, and within their own social organizations